Megaprostheses and custom-made implants in complex cases of revision surgery after TKA - Troiano, Elisa; Mondanelli, Nicola; Peri, Giacomo; Facchini, Andrea; Nuvoli, Nicolò; Giannotti, Stefano (Lo Scalpello - Journal, 2021)
The use of megaprostheses or custom-made devices is an established treatment for or- thopedic malignancies, but their indication has been expanded to some non-neoplastic conditions such as complex cases of re-revision surgery or failed osteosynthesis. A con- secutive series of 5 patients were treated with megaprostheses as a solution for complex cases of re-revision surgery around the knee joint. Each patient was assessed clinically and radiographically at 1, 3, 6, and 12 months after surgery. One patient died for intestinal infarc- tion after surgery. The 4 remaining patients resumed gait and knee function. We did not observe infections or mobilizations of the implants, and the only complication we described was patellar dislocation of the extensor mechanism when the implant with proximal tibia resection was used. Complex re-revision surgery after TKA represents a major challenge for the orthopedic surgeon due to poor bone stock and the presence of prosthetic revision components. The implant of megaprostheses or custom-made devices can play a crucial role in these rare but complex cases of non-oncological orthopedic surgery ensuring early functional recovery.